Motor recovery of stroke patients after rehabilitation: one-year follow-up study - Vilai Kuptniratsaikul (2018)
Copyright © 2016 Informa UK Limited, trading as Taylor & Francis Group. Purpose To investigate motor recovery of stroke patients 1 year after rehabilitation. Materials and Methods A cross-sectional study of 192 stroke patients discharged from rehabilitation wards in nine tertiary hospitals was conducted. Motor recovery was assessed using the Brunnstrom motor recovery stages (BMRS), at 6 and 12 months after discharge. Factors related to the BMRS of the hand, arm and leg were analyzed. Results The mean age of patients was 62.2 years (57.3% male). Significantly more patients presented improvement of at least one BMRS of the hand, arm and leg compared with those with decreasing BMRS (p < 0.001). The percentage of patients with BMRS III– VI at 6 months was greater than that at discharge, but the recovery at 12 months was slightly higher than that at 6 months. It seems that motor recovery from stroke was near maximal at six months. Regarding the factors related to motor recovery, only lengths of stay (LOS) < 30 d during the first admission and Barthel index at discharge ≥10 were related to the improvement of BMRS of the hand, arm and leg on multivariate analysis. Additionally, no complication at discharge was associated with the improvement of BMRS of the leg. Conclusions Approximately half of our stroke patients had motor improvement of at least one stage of BMRS at one year. Motor recovery after stroke at the end of the first year was associated with shorter LOS during the first admission, higher discharge Barthel index score and absence of complications at discharge.